In-situ X-ray micro-computed tomography imaging of the microstructural changes in water-bearing medium rank coal by supercritical CO2 flooding - Zhang, Y.; Lebedev, Maxim; Jing, Y.; Yu, H.; Iglauer, Stefan (Elsevier BV, 2019)
© 2019 Elsevier B.V. Carbon dioxide geosequestration into deep unmineable coal seams is a technique which can mitigate anthropogenic greenhouse gas emissions. However, coal composition is always complex, and some minerals such as calcite chemically react when exposed to the acidic environment (which is created by scCO2 mixing with formation water). These reactive transport processes are still poorly understood. We thus imaged a water-bearing heterogeneous coal (calcite rich) core before and after scCO2 injection in-situ at high resolution (3.43 µm) in 3D via X-ray micro-tomography. Indeed, the calcite- fusinite mix phase was partially dissolved, and absolute porosity and connectivity significantly increased. We thus suggest that such a process could be used as an acidizing method for enhanced coal bed methane (ECBM) production, thus significantly improving the permeability performance, CO2 injectivity and the associated methane permeability.